Studies on encapsulation of tocotrienolrich fraction of palm oil in nanoemulsion using high-energy emulsification / Elcy Goh Pik Seah - Elcy Goh , Pik Seah (2019)
Oil-in-water nanoemulsion has become a promising approach to improve the solubility and bioavailability of tocotrienols by enhancing its absorption across intestinal tract thus improving therapeutic efficacy during oral administration. In this study, nanoemulsions from palm-based tocotrienol-rich fraction (TRF) were prepared by employing ultrasonication and microfluidics. Nanoemulsions with average droplet size of 104.1 ± 2.9 nm with polydispersity index (PDI) of 0.215 ± 0.008 were obtained after sonification for 80 min at amplitude of 100%. However, increasing the sonication duration led to ‘over-processing’. Results revealed that different types of emulsifier combination had a significant (p < 0.05) effect on particle size and PDI. The mixing of Tween 80-Brij 35 (50:50 w/w) at a concentration of 1.5% (w/v) produced an average droplet size of 54.8 ± 1.2 nm and PDI of 0.266 ± 0.006. Increasing the concentration of emulsifier from 0.75% to 3% (w/v) resulted in a significant reduction (p < 0.05) in average droplet size, but a significant increase in polydispersity index (p < 0.05). Nonetheless, increasing emulsifier concentrations to 3% (w/v) from 0.75% (w/v) led to a high PDI (0.404 ± 0.002) indicating that droplet size distribution became less monodisperse. Droplet size obtained through microfluidization revealed that average droplet size after 10 passes of homogenization with increasing pressure was found to decrease from 120 ± 2.6 to 65.1 ± 0.2 nm. Overall, the PDI value obtained from the resulting nanoemulsions was smaller than 0.2 indicating a narrow size distribution. Compared to microfluidics, average droplet size obtained using ultrasonication was larger. The average droplet size of nanoemulsion produced by ultrasonication extended from 139 ± 3.0 to 160.5 ± 10.5 nm with PDI ranging between 0.205 ± 0.015 – 0.239 ± 0.013. Nanoemulsions stabilized with Tween series alone or emulsifier blend Brij 35: Span 80 (0.6:0.4 w/w) produced droplet size less than 100 nm. Overall the percentage of tocols degraded during processing varying from 3.9 to 25.1 %, significantly (p < 0.05) influenced by the type of emulsifiers used. Nanoemulsions containing TRF fabricated using microfluidics underwent external gelation with calcium ions as cross-linker to form solid hydrogel bead using alginate alone or a blend of alginate with gum Arabic (GA) or alginate with hydroxyl propyl methyl cellulose (HPMC). Observations revealed that encapsulation efficiency of TRF entrapped within 2% (w/v) sodium alginate (SA) was 50.2 ± 1.2%. Addition of 0.5% or 1% (w/v) of HPMC into 2% (w/v) SA, gave TRF encapsulation efficiency of 52.9 ± 2.1 % and 56.7 ± 1.5%, respectively. Whereas addition of 2.5% or 5 % (w/v) GA into 2% (w/v) SA, produced an encapsulation efficiency of 60.5 ± 1.5% and 13.9 ± 0.8%, respectively. In conclusion, the results showed that nanoemulsion formed by microfluidics is relatively simple omitting the use of organic solvent. Emulsification through microfluidics was more effective compared to ultrasonication as droplets size obtained was smaller. Encapsulation efficiency of TRF obtained using different type of wall material was in the range between 13.9% and 60.5%.